A Simulation Study on the Growth of Oviduct Mucosa Cells in the Uterine Cavity Microenvironment - Wu CR; Cai HL; Cai DX; Li TL; Shen R; Zi D (Dove Medical Press, 2021)
Cheng-Rong Wu,1 Hua-Lei Cai,2 Di-Xian Cai,3 Tao-Lan Li,1 Rong Shen,2 Dan Zi2 1Department of Obstetrics and Gynecology, Guizhou Medical University, Guiyang, 550004, People's Republic of China; 2Department of Obstetrics and Gynecology, The Affiliated Hospital of Guizhou Medical University, Guiyang, 550004, People's Republic of China; 3Department of Psychology, Guizhou Medical University, Guiyang, 550004, People's Republic of ChinaCorrespondence: Hua-Lei CaiDepartment of Obstetrics and Gynecology, The Affiliated Hospital of Guizhou Medical University, No. 28 of Guiyi Street, Yunyan District, Guiyang, 550004, People's Republic of ChinaTel +86 18198132660Fax +86 851-86855119Email caihualei_dr@163.comObjective: The growth of oviduct mucosa in the uterine cavity was observed by co-culture of oviduct mucosa cells and endometrial cells in different proportions to study the possibility and function of the growth of oviduct mucosa in the uterine cavity.Methods: The extracted cells were identified by immunofluorescence with cytokeratins 19 (CK19) and vimentin. A Cell Counting Kit-8 (CCK8) experiment, cell decidualization induction, and HE staining were performed after the co-culture of two kinds of cells in different proportions.Results: 1) The cells could grow normally when the two cells were co-cultured indirectly. 2) A CCK8 test of oviduct mucosa cells showed that the growth rate of each group was similar after the indirect co-culture of two kinds of cells in different proportions, which was in line with the growth law of normal cells. 3) Immunofluorescence identification of the cells showed that most of the two kinds of cells in the second passage were CK19 positive and were epithelial cells, while most of the cells in the fifth passage expressed positive vimentin antibody and were stroma cells. 4) After cell decidualization induction, the cell morphology of each group showed deciduation-like changes. 5) After decidualization, the cell morphology of each group was similar after HE staining.Conclusion: Oviduct mucosa cells can grow normally in the uterine environment. In the uterine environment with different degrees of endometrial loss, the growth rate of oviduct mucosa cells is not inhibited. Its morphology does not change, and it can undergo decidualization in vitro.Keywords: oviduct mucosa, endometrium, co-culture, endometrial receptivity, intrauterine adhesion